Disease heterogeneity, prognostication and the role of targeted therapy in multiple myeloma. Issue 13 (10th November 2021) - Zanwar, Saurabh; Kumar, Shaji
Abstract: Multiple myeloma (MM) is a clonal plasma cell malignancy with a heterogeneous disease course. Insights into the genetics of the disease have identified certain high-risk cytogenetic features that are associated with adverse outcomes. While the advances in therapy have translated into dramatic improvements in the outcome of patients with MM, those with high-risk genetic features continue to perform poorly. This has resulted in a need for clinical trials focusing on the high-risk subgroup of MM as they search for additional biomarkers and therapeutic targets continue. In this review, we discuss the currently existing data on prognostic and predictive biomarkers in MM and speculate the role of treatment stratification based on the genetic features of the disease.